2019
DOI: 10.1088/2053-1583/ab1a4c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and liquid phase exfoliation of cylindrite: a natural van der Waals superlattice with intrinsic magnetic interactions

Abstract: We report the isolation of thin flakes of cylindrite, a naturally occurring van der Waals superlattice, by means of mechanical and liquid phase exfoliation. We find that this material is a heavily doped p-type semiconductor with a narrow gap (<0.85 eV) with intrinsic magnetic interactions that are preserved even in the exfoliated nanosheets. Due to its environmental stability and high electrical conductivity, cylindrite can be an interesting alternative to the existing two-dimensional magnetic materials.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 54 publications
3
37
2
Order By: Relevance
“…The franckeite is composed of a series of isotropic 2D layers, but it exhibits a spontaneous rippling that makes the material structurally anisotropic. [ 32,33 ] It has been recently shown that the rippling structure of franckeite comes hand in hand with an inhomogeneous in‐plane strain profile and anisotropic electrical, vibrational, and optical properties. [ 34 ] However, there are few reports on the optical response and application of the layered franckeite, especially in the nonlinear optical regime with increasing incident light intensity.…”
Section: Figurementioning
confidence: 99%
“…The franckeite is composed of a series of isotropic 2D layers, but it exhibits a spontaneous rippling that makes the material structurally anisotropic. [ 32,33 ] It has been recently shown that the rippling structure of franckeite comes hand in hand with an inhomogeneous in‐plane strain profile and anisotropic electrical, vibrational, and optical properties. [ 34 ] However, there are few reports on the optical response and application of the layered franckeite, especially in the nonlinear optical regime with increasing incident light intensity.…”
Section: Figurementioning
confidence: 99%
“…Elements of the unit cell Modulation by (dimension) Applications (ref. ) Vertical stacking Chemical composition, lattice (mis)match (1D) IR photodetectors 15,16,20 Phase-change memory [28][29][30][31][32][33][34] Thermoelectrics [47][48][49][50] Superconductivity [51][52][53][54] Intercalated compounds Chemical composition, structuring, charge transfer (1D)…”
Section: Classificationmentioning
confidence: 99%
“…Natural van der Waals superlattices have been obtained by isolating thin layers from minerals such as franckeite [15][16][17][18][19] or cylindrite. 20 Both minerals belong to the family of sulfosalts with the general formula (Pb,Sn) 6+x…”
Section: D Materials Superlatticesmentioning
confidence: 99%
See 2 more Smart Citations